The extracellular vesicles in HIV infection and progression: mechanisms, and theranostic implications - Tang, Zhen; Lu, Yao; Dong, Jiu-Long; Wu, Wen; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2024)
Extracellular vesicles (EVs), these minute yet mighty cellular messengers are redefining our understanding of a spectrum of diseases, from cancer to cardiovascular ailments, neurodegenerative disorders, and even infectious diseases like HIV. Central to cellular communication, EVs emerge as both potent facilitators and insightful biomarkers in immune response and the trajectory of disease progression. This review ventures deep into the realm of EVs in HIV-unraveling their pivotal roles in diagnosis, disease mechanism unravelling, and therapeutic innovation. With a focus on HIV, we will highlights the transformative potential of EVs in both diagnosing and treating this formidable virus. Unveiling the intricate dance between EVs and HIV, the review aims to shed light on novel therapeutic strategies that could significantly benefit HIV therapy, potentially even leading to the eradication of HIV.